2019
DOI: 10.1152/ajprenal.00533.2018
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of renal ischemia-reperfusion injury solely induced by cold ischemia

Abstract: Transplanted kidneys usually experience several episodes of ischemia, including cold ischemia during allograft storage in preservation solution. However, previous studies focusing on cold renal ischemia were only carried out in vitro or ex vivo. In the present study, we developed and characterized an in vivo mouse model of renal ischemia-reperfusion injury (IRI) induced exclusively by cold ischemia. C57BL/6 mice underwent right kidney nephrectomy, and the left kidney was kept cool with circulating cold saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…In this study, we have provided the first evidence for PKCd regulation of kidney injury in cold-storage transplantation, a model relevant to cold ischemia reperfusion. 16,[49][50][51] We show that kidney injury due to cold storage-associated transplantation was markedly reduced when PKCd was ablated in donor kidneys (Figure 6), indicating an essential role of renal intrinsic PKCd. In line with this observation, we detected PKCd activation in kidney tissues, especially in renal tubules (Figure 2).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we have provided the first evidence for PKCd regulation of kidney injury in cold-storage transplantation, a model relevant to cold ischemia reperfusion. 16,[49][50][51] We show that kidney injury due to cold storage-associated transplantation was markedly reduced when PKCd was ablated in donor kidneys (Figure 6), indicating an essential role of renal intrinsic PKCd. In line with this observation, we detected PKCd activation in kidney tissues, especially in renal tubules (Figure 2).…”
Section: Discussionmentioning
confidence: 85%
“…However, in the ex vivo setting, hypothermic preservation tended to reduce damage more than subnormothermic temperatures. In a mouse model, experiments with solely cold ischemia showed detrimental kidney damage [52]. Yet, the most suitable preservation temperature depends on many factors and temperature optimization for kidney preservation will require more thorough investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research (6,7) and clinical trial (8) revealed that inhibition of proximal tubular cell death with caspase inhibitors during cold storage improves graft function and histology. Moreover, we (9) and others (10)(11)(12)(13) identified intrinsic mitochondrial pathway of apoptosis in cold storage/transplantation kidney injury. Despite these findings, the cellular and molecular mechanism of cold storage/transplantation kidney injury remains elusive and there is an urgent need for effective renoprotective approaches.…”
Section: Introductionmentioning
confidence: 72%